Cardiovascular morbidity and risk factors of cardiovascular events in the Russian Federation - I. V. Samorodskaya (Кардиоваскулярная терапия и профилактика, 2005)
Based on registry statistics, the author analyzes dynamics and structure of cardiovascular morbidity in Russian adults for the period 1993-2003. Russian and international data are reviewed, and cardiovascular risk factor prevalence is compared.